Some physical characteristics of Sambar Deer (Cerous unicolor) - Idris, Ismail; Moin, Saidi; Sulah, Samto; Jiwan, Dawend (Universiti Putra Malaysia Press, 2000)
Weights and body measurements of 115 sambar deer (Cervus unicolor) from three states of Malaysia were analysed. The deer range in age from three weeks to seven years old. They were divided into groups and allowed to graze the fenced up paddocks. The deer which were raised in an environment similar to their natural habitat had the heaviest body weight (100.18 kg). The effects of location and partial regression of body height, body length and heart girth, had highly significant (p<.00l) effects on body weight. The partial regression coefficients for body weight, body length and heart girth were 0.91, 0.84 and 1.00, respectively.